Estimation of costs in the Russian public procurement system. (2017) - Balaeva, Olga; Yakovlev, Andrei
The growing attention of governments, international organisations and NGOs to public procurement issues over the last two decades has been accompanied by many studies on the efficiency of public procurement. However, few researchers have considered the costs of procurement regulation for public customers and private suppliers. This problem is especially acute for the public procurement system in Russia. In this paper we propose an approach to measuring public customers' procurement costs. We test this approach with the data on a large Russian public customer: Voronezh State University. We show that the proposed approach is universal and can be applied at a micro level by other public customers to measure the efficiency of their procurement and to optimise the costs. This approach can also be used as a basis for a larger inquiry into the costs and effectiveness of procurement at the level of regional authorities or sectoral ministries.